The Role of Wakif in Waqf Development in KM 05 Village, Blambangan Umpu District, Way Kanan Regency - Nabila Citra Safira; Yevi Safitri; Nurman Angkasa; Muhammad Anggi Febri Saputra; Deden Nurkholis (STIS Sultan Fatah, 2026)
Waqf is an Islamic philanthropic instrument with significant potential to support social and economic development. However, existing studies on productive waqf have predominantly focused on the role of nazhir (waqf managers), while the involvement of wakif (donors) in waqf development has received limited scholarly attention. This study aims to analyze the role of wakif in waqf development in Blambangan Umpu KM 05 Village, Way Kanan Regency, identify the constraints affecting the optimization of their role, and formulate strategies to enhance their participation in productive waqf development. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation involving 15 informants consisting of wakif, nazhir, religious leaders, village officials, and beneficiaries. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings reveal that the role of wakif remains largely limited to the donation stage and has not been optimally extended to planning, supervision, or the development of waqf assets. The main challenges include limited literacy regarding productive waqf, the dominance of consumptive perceptions of waqf, inadequate managerial capacity of nazhir, and insufficient institutional support. This study further finds that wakif possess substantial social capital that can be optimized as strategic partners in productive waqf development through collaborative engagement with nazhir. The study contributes conceptually by proposing a strengthened wakif–nazhir collaboration model as a community-based strategy for developing productive waqf in rural areas.